MEDIA PODCAST SAKURA TIPS AS A MEDIA FOR LEARNING BASIC LEVEL OF JAPANESE LEARNING - Rizky Nur Azizah; Nana Rahayu; Yenny Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the use of the Sakura Tips podcast media in learning to listen to Japanese at the basic level. This research is a qualitative research with this type of observational research. The sample in this study was 20 Japanese Language Education students Class of 2021 in listening lessons. The results of the study can be concluded that the Sakura Tips podcast media can be used as a medium for learning to listen to basic Japanese because it can be seen from the student learning process on the podcast media that is played. It is hoped that Japanese language learners can become independent learning media so that they can improve their ability to learn Japanese. For further research using the Sakura Tips podast media in learning sentence patterns and looking for podcast topics with more interesting innovations can increase the interest of Japanese language learners.Key words: Media podcast, Listening, Basic Level